Analysis Of Errors In Translating English Collocations Into Uzbekistan - Rakhmanova, Nilufar Bakhodirovna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
The process of globalization and the strengthening of the position of the English language as a means of international communication have sharply increased the need for translation activities. Today, translation from English into Uzbek occupies an important place not only in the activities of professional translators, but also in the activities of students, teachers and researchers studying in higher educational institutions. In this process, the issue of correct understanding and adequate translation of the lexical features of the English language, especially collocations, is becoming an urgent problem.